Novel Therapeutic Approaches for KRAS-Mutated Lung Cancer Involving LZTR1 Genetic Alteration - Raj N. Sewduth; Tonci Ivanisevic; Peihua Zhao; Anna A. Sablina (Medical Sciences Forum, 2023)
A total of 30% of lung adenocarcinoma are driven by activating KRAS mutations. The treatment options for KRAS-mutant lung cancer are still limited as a challenge for therapy is the high heterogeneity within KRAS mutant tumors. Co-existing genetic events alter RAS signaling, such as the genetic alteration of the ubiquitin ligase leucine zipper-like transcriptional regulator 1 (LZTR1). LZTR1 is an adaptor of CUL3 E3 ligase that controls the localization and expression levels of RAS proteins by regulating their ubiquitination. Recent studies demonstrated that the loss of LZTR1 leads to resistance to the tyrosine kinase inhibitor and the multi-kinase inhibitor, suggesting that LZTR1 loss might be associated with the drug resistance of KRAS-mutated lung tumors. TCGA analysis indicated that LZTR1 loss affected progression survival in KRAS mutant LUAD patients, with a significant co-occurrence of LZTR1 loss and KRAS mutations. While LZTR1 depletion in LUAD cell lines did not affect proliferation in the cell culture, the knock-out (KO) of Lztr1 in a mouse model with Kras G12D oncogenic mutations caused a clear and significant acceleration of tumor progression in the Lztr1 loss groups, indicating that Lztr1 can affect tumor onset and progression. To study the alterations of the RAS pathway triggered by LZTR1 loss, we performed a global OMICS analysis on both in vitro and in vivo systems, identifying potential therapeutic targets. The characterization of immune populations in the tumors of flow cytometry also revealed changes in immune infiltrate in the KO mouse. We are now investigating how the changes caused by Lztr1 deletion on KRAS signaling heterogeneity within tumor cells can affect the tumor microenvironment composition. Our results suggest that the dysregulation of KRAS function by Lztr1 deletion contributes to cancer progression by affecting tumor cell communication with the microenvironment. Our work could explain how Lztr1 loss can affect drug response and lead to therapy resistance.